The Relationship between Emotional Intelligence and Innovative Work Behavior in Government Agency Employees - Bakri, Bakri; Choerudin, Achmad; Sono, Mohammad Gifari (West Science Business and Management, 2025)
This study examines the relationships between Emotional Intelligence (EI), Innovative Work Behavior (IWB), and Employee Performance (EP) among government employees in Indonesia using a quantitative approach. Data were collected from 100 respondents through a Likert-scale questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that EI significantly influences both IWB and EP, while IWB also has a direct positive effect on EP. Furthermore, IWB mediates the relationship between EI and EP, underscoring its critical role in translating emotional capabilities into improved performance outcomes. The results highlight the importance of fostering EI and IWB to enhance employee performance in government institutions. This study provides theoretical insights and practical recommendations for public sector managers aiming to improve innovation and productivity in the workplace.